Mechanisms of Weight Regain following Weight Loss - Blomain, Erik Scott (Hindawi Publishing Corporation, 2013)
Obesity is a world-wide pandemic and its incidence is on the rise along with associated comorbidities. Currently, there are few effective therapies to combat obesity. The use of lifestyle modification therapy, namely, improvements in diet and exercise, is preferable over bariatric surgery or pharmacotherapy due to surgical risks and issues with drug efficacy and safety. Although they are initially successful in producing weight loss, such lifestyle intervention strategies are generally unsuccessful in achieving long-term weight maintenance, with the vast majority of obese patients regaining their lost weight during followup. Recently, various compensatory mechanisms have been elucidated by which the body may oppose new weight loss, and this compensation may result in weight regain back to the obese baseline. The present review summarizes the available evidence on these compensatory mechanisms, with a focus on weight loss-induced changes in energy expenditure, neuroendocrine pathways, nutrient metabolism, and gut physiology. These findings have added a major focus to the field of antiobesity research. In addition to investigating pathways that induce weight loss, the present work also focuses on pathways that may instead prevent weight regain. Such strategies will be necessary for improving long-term weight loss maintenance and outcomes for patients who struggle with obesity.